2011
DOI: 10.1111/j.1365-246x.2010.04906.x
|View full text |Cite
|
Sign up to set email alerts
|

Theory of multisource crosstalk reduction by phase-encoded statics

Abstract: S U M M A R YFormulas are derived that relate the strength of the crosstalk noise in supergather migration images to the variance of time, amplitude and polarity shifts in encoding functions. A supergather migration image is computed by migrating an encoded supergather, where the supergather is formed by stacking a large number of encoded shot gathers. Analysis reveals that for temporal source static shifts in each shot gather, the crosstalk noise is exponentially reduced with increasing variance of the static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…We simulate 256 shots using the true velocity model shown in Figure 3(a). Each shot is recorded with 512 receivers at a 20 m receiver interval with a total recording time of 10 s. We assume a fixed-spread acquisition geometry for both the sources and the receivers and blend all the 256 shotgathers into one supergather using the dynamic polarity and phase-encoding technique proposed by Schuster et al (2011) and Dai et al (2012). The velocity model shown in Figure 3(b) is used as the migration velocity model.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We simulate 256 shots using the true velocity model shown in Figure 3(a). Each shot is recorded with 512 receivers at a 20 m receiver interval with a total recording time of 10 s. We assume a fixed-spread acquisition geometry for both the sources and the receivers and blend all the 256 shotgathers into one supergather using the dynamic polarity and phase-encoding technique proposed by Schuster et al (2011) and Dai et al (2012). The velocity model shown in Figure 3(b) is used as the migration velocity model.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This approach, although very effective in reducing the computational cost, suffers from crosstalk noise which severely degrades the quality of the migrated image. Later, Dai and Schuster (2009) and Schuster et al (2011) extended the blended source migration technique to multisource least-squares migration and showed that the crosstalk noise can be mitigated by an iterative migration of supergathers.…”
Section: Introductionmentioning
confidence: 99%
“…Schuster et al (2011), Dai et al (2012 employed a phase-encoding multisource approach to increase the computational efficiency. Dai and Schuster (2013), Li et al (2014a, b) performed plane-wave encoding to LSRTM and achieved a better suppression to crosstalk.…”
Section: Introductionmentioning
confidence: 99%
“…However, the random encoding functions used by Romero et al (2000), Krebs et al (2009), Schuster et al (2011) and Dai et al (2012), cannot be easily applied to a seismic survey with a marine streamer geometry (Routh et al, 2011;Huang and Schuster, 2012) because, although the calculated synthetic data are of fixed spread geometry, the observed data are recorded with a marine streamer geometry. Huang and Schuster (2012) proposed a frequency-selection encoding strategy for least-squares phase shift migration, which is applicable to marine data.…”
Section: Introductionmentioning
confidence: 99%
“…The phase-encoding technique (Romero et al, 2000;Krebs et al, 2009;Schuster et al, 2011) has been applied to increase the computational efficiency of seismic modeling and migration and it can reduce the cost of LSRTM to the level of conventional RTM. However, the random encoding functions used by Romero et al (2000), Krebs et al (2009), Schuster et al (2011) and Dai et al (2012), cannot be easily applied to a seismic survey with a marine streamer geometry (Routh et al, 2011;Huang and Schuster, 2012) because, although the calculated synthetic data are of fixed spread geometry, the observed data are recorded with a marine streamer geometry.…”
Section: Introductionmentioning
confidence: 99%